Defining the usability of query performance : an experimental approach / Aida Zuliana Abdul Wahab - Abdul Wahab, Aida Zuliana (Faculty of Computer and Mathematical Sciences, 2007)
Prior research on human ability to write database queries has concentrated on the characteristics of query interfaces and the complexity of the query tasks. This paper reports the results of a laboratory experiment that investigated the relationship between user characteristics and query types on performance by using Ms Access and MySQL database systems. This relationship is not investigated in earlier database research, while controlling the query interface, data model, technology, and training. By using two types of database systems in this research which is Ms Access and MySQL, is important to compare which database system is easier, comfortable to use and meet the project requirements of the users. This report also discuss about the effect of database query types on task performance. Finally, task complexity was found to be the main determinant of user confidence. The implications of this result for future research and practice are discussed.